2018
DOI: 10.1111/ijcp.13270
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of global long interspersed nucleotide element‐1 ( LINE ‐1) DNA methylation in a longitudinal cohort of type 2 diabetes mellitus (T2 DM ) individuals

Abstract: Introduction Recent studies have indicated that methylation of the LINE‐1 elements is associated with an increased risk of worsening carbohydrate metabolism. It has been shown that overall DNA methylation of LINE‐1 elements could be considered as a risk factor for T2DM and its complications, independent of other established risk factors. Methods A total of 794 T2DM individuals from Salford, UK were included in this study (60% men n = 470). All patients had clinical and metabolic variables measured in 2002 (bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Malipatil et al, in their study reported that an increase of 10 % in LINE-1 methylation was associated with decreased cholesterol/HDL ratio by 0.4 mmol/L in the overall sample of men and women. However, when stratifying by sex, the inverse association remained significant only in women [25]. In an EWAS performed by Garcia-Calzon et al, female samples displayed on average higher methylation in the X-chromosome, whereas males presented higher methylation in the autosomes.…”
Section: Blood Lipidsmentioning
confidence: 91%
See 3 more Smart Citations
“…Malipatil et al, in their study reported that an increase of 10 % in LINE-1 methylation was associated with decreased cholesterol/HDL ratio by 0.4 mmol/L in the overall sample of men and women. However, when stratifying by sex, the inverse association remained significant only in women [25]. In an EWAS performed by Garcia-Calzon et al, female samples displayed on average higher methylation in the X-chromosome, whereas males presented higher methylation in the autosomes.…”
Section: Blood Lipidsmentioning
confidence: 91%
“…Global DNA methylation is a frequent used marker for epigenetic screening since it captures the DNA methylation also at unknown genetic locations while the results of average DNA methylation correlate with the methylation of some trait-relevant genes [23,24]. Ten articles [14,[25][26][27][28][29][30][31][32][33] investigated sex-specific associations between DNAm and blood lipid concentrations applying global n = 2, epi-genome wide n = 1 and candidate gene n = 7 approaches. In total 2,443 non-overlapping participants 1,174 women and 1,269 men from USA, Canada, Finland, UK and China were included in these studies.…”
Section: Blood Lipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…LINE-1 sequences are highly repeated human DNA sequences that constitute about 17% of the human genome [84] and the degree of LINE-1 DNA methylation may provide a link between environmental exposure and development of cardiovascular complications of T2DM independently of other classical risk factors [85]. Indeed, higher levels of LINE1 methylation have been associated to a reduction in cholesterol/HDL cholesterol ratio and considered predictive of less weight gain over time and subsequent lower body mass index (BMI) in female patients [86].…”
Section: Epigenetic Changes In T2dm-related Endothelial Dysfunctionmentioning
confidence: 99%